(untitled) (Community Based Medical Journal, 2018)
Lacrimal Sac tumors are extremely rare and potentially life threating. It may be primary, secondary and metastasis from distant organ. Lacrimal sac tumors may be broadly classified into epithelial (72%), mesenchymal (12%), lymphoproliferative (11%) and melanocytic (04%). About 72% are malignant; tend to be locally invasive with high recurrence rate. To report three cases of rare primary lacrimal sac tumors. We evaluated three rare case reports on primary lacrimal sac tumors in two tertiary eye hospitals in Bangladesh. 46 year old female, 36 year old male, and a 21-year-old young male, patients presented with mass in the lacrimal sac area. Two of them underwent deep incision biopsy and histopathology revealed Low grade extranodal marginal zone lymphoma (ENMZL). One patient was treated with Radiotherapy and another one with 6-Cycles of CHOP chemotherapy(Cyclophosphamide, Hydroxydaunorubicin, Oncovin,Prednisone). One patient underwent excision biopsy and histopathology reported lacrimal sac haemangiopericytoma. In all cases the lesions were resolved completely. Management of lacrimal sac tumors requires a high index of suspicion, as these are fatal tumor and often misdiagnosed as dacryocystitis. Early and appropriate intervention will help to complete resolution of the tumor as well as to reduce the recurrence. CBMJ 2018 July: Vol. 07 No. 02 P: 45-49